Defect formation on diffusive layers of ZnSe:Sn and ZnSe:Mg - Gryvul, V.I.; Makhniy, V.P.; Tkachenko, I.V. (Functional Materials, 2007)
Equilibrium concentrations of point defects in ZnSe layers obtained by Sn and Mg diffusion fron vapor phase at 1150 K have been calculated using the quasi-chemical reaction method. The calculated results are compared to data obtained fron thermo-e.m.f., conductivity and luminescence spectra measurements.